Pengaruh Kualitas Produk dan Citra Merek Terhadap Keputusan Pembelian Mobil Xenia di Dealer Daihatsu Lippo Cikarang - Robbani, Hamzah; Syam, Radian (LITERATUS, 2024)
This study explores the legal implications of the postponement of the halal certification requirement in Indonesia's tourism sector until 2026, focusing on strengthening the authority of the Halal Product Assurance Agency (BPJPH) in supervising and enforcing halal standards. This postponement creates significant challenges in the application of the Lex Superior Derogat Legi Inferiori principle and results in a legal vacuum (rechtsvacuum) that could undermine legal certainty. The study employs a descriptive approach with qualitative analysis involving in-depth interviews with BPJPH officials and constitutional law academics, as well as a review of documents related to halal regulations. The findings indicate that the postponement of halal certification negatively impacts regulatory compliance, damages Indonesia's image as a halal tourism destination, and necessitates strict legal measures to address the legal vacuum and strengthen BPJPH's authority. Practical recommendations are provided to enhance oversight and law enforcement to maintain the integrity of halal standards in Indonesia during this postponement period.